Aberrant Expression of CXCR4 Significantly Contributes to Metastasis and Predicts Poor Clinical Outcome in Breast Cancer - Yang, P.; Liang, S.-X.; Huang, W.-H.; Zhang, H.-W.; Li, X.-L.; Xie, L.-H.; Du, C.-W.; Zhang, G.-J. (Current Molecular Medicine, 2014)
Triple negative breast cancer is known for its visceral metastasis. We have found that CXCR4 is overexpressed in triple negative breast cancer and is associated with visceral metastasis. We further investigated whether CXCR4 is a prognostic factor affecting survival following visceral metastasis in breast cancer patients. Our results indicate that increased CXCR4 expression among breast cancer patients with visceral metastasis was positively correlated with poor overall survival (P<0.001). Silencing of CXCR4 was associated with a decrease in the tumorigenic properties of MDA-MB-231 breast cancer cells, caused reversion of EMT and suppression of MMP-9, increased apoptosis, and caused a reduced incidence of tumor lung metastasis in mice. These results are indicative of CXCR4 having a predictive role in patients with visceral metastasis and indicate that shRNA knock down of CXCR4 might be a novel therapeutic strategy to prevent breast cancer metastasis when CXCR4 is overexpressed.
Keywords: Apoptosis